2020
DOI: 10.3390/antiox9080689
|View full text |Cite
|
Sign up to set email alerts
|

d-Galactose Decreases Anion Exchange Capability through Band 3 Protein in Human Erythrocytes

Abstract: d-Galactose (d-Gal), when abnormally accumulated in the plasma, results in oxidative stress production, and may alter the homeostasis of erythrocytes, which are particularly exposed to oxidants driven by the blood stream. In the present investigation, the effect of d-Gal (0.1 and 10 mM, for 3 and 24 h incubation), known to induce oxidative stress, has been assayed on human erythrocytes by determining the rate constant of SO42− uptake through the anion exchanger Band 3 protein (B3p), essential to erythrocytes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 68 publications
(119 reference statements)
3
20
1
Order By: Relevance
“…In these experimental conditions, the rate constant for SO 4 2− uptake was accelerated and, in parallel, SO 4 2− uptake was significantly reduced (Figure 1 and Table 1). This finding appears to be in disagreement with what was reported by our group in a recent study (Remigante et al, 2020), where the exposure of erythrocytes to 10 mmol/L D-Gal for 24 h has been observed to induce a reduction (0.051 ± 0.001 in 19.60 min) of the rate constant for SO 4 2− uptake, not accompanied by lipid peroxidation, oxidation of -SH membrane groups, alteration of GSH/GSSG ratio, or MetHb formation (Remigante et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In these experimental conditions, the rate constant for SO 4 2− uptake was accelerated and, in parallel, SO 4 2− uptake was significantly reduced (Figure 1 and Table 1). This finding appears to be in disagreement with what was reported by our group in a recent study (Remigante et al, 2020), where the exposure of erythrocytes to 10 mmol/L D-Gal for 24 h has been observed to induce a reduction (0.051 ± 0.001 in 19.60 min) of the rate constant for SO 4 2− uptake, not accompanied by lipid peroxidation, oxidation of -SH membrane groups, alteration of GSH/GSSG ratio, or MetHb formation (Remigante et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to what was performed in the previous investigation (Remigante et al, 2020) and to better explain the altered functional mechanism observed in the present experiments, lipid peroxidation and oxidation of membrane -SH groups, mainly belonging to B3p (Roy et al, 2005) & Zakaria, 2019). These findings suggest that 25 mmol/L D-Gal represents a threshold value for differential effects on B3p.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…82 OS plays a fundamental role in the pathophysiology of galactosemia, which is also characterized by the formation of glycated haemoglobin. [82][83][84] Remigante et al 85 have reported that the rate constant for SO 4 2− uptake via…”
Section: Slc4a1 and Oxidative Stressmentioning
confidence: 99%
“…Despite d-Gal being known to induce oxidative stress, exposure of erythrocytes to relatively low (0.1–10 mM) d-Gal concentrations led to a reduced anion exchange capability independent from oxidative stress, but rather linked to glycated Hb production. This study sheds light on the early effects of excessive d-Gal on membrane transport systems and possible complications related to undiagnosed galactosemia [ 2 ].…”
mentioning
confidence: 99%